The Primer Generator: A Program that Facilitates the Selection of Oligonucleotides for Site-Directed Mutagenesis. (April 1999) - Turchin, Alexander; Lawler, Joseph F.
Site-directed mutagenesis is a powerful tool that has enabled molecular biologists to perform functional analysis of altered nucleic acids and proteins. Newer PCR-based mutagenesis techniques have reduced the process of mutagenesis to as little as one day. While each technique has its advantages, both require a strategy to isolate the desired clone from a population that contains mutagenized and wild-type genes. In this report, we describe a World Wide Web-based computer program that facilitates the design of mutagenic primers such that successfully mutagenized clones can be identified by the presence or absence of a unique restriction site.